2013
DOI: 10.1287/mnsc.2013.1732
|View full text |Cite
|
Sign up to set email alerts
|

Blogs, Advertising, and Local-Market Movie Box Office Performance

Abstract: We measure the effects of pre- and postrelease blog volume, blog valence, and advertising on the performance of 75 movies in 208 geographic markets in the United States. We attribute the variation in blog effects across markets to differences in demographic characteristics of markets combined with differences across demographic groups in their access and exposure to blogs as well as their responsiveness conditional on access. We study the effects of prerelease factors on opening day box office performance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 32 publications
0
98
0
Order By: Relevance
“…The findings reported impact of online buzz valence on dependent variable, i.e., weekly box office revenue. In comparison, more recent studies reported in a blog analyses that box office ticket sales of movies can be affected by the valence of online buzz information collected from Yahoo Movie and blog posts (Gopinath, Chintagunta, and Venkataraman, 2013). Chen, Stephen (2001) in the research work of assessing the impact of internet on brands claims that easy access to online customer reviews has led some audiences (consumers) to suggest that alternative assurances of product quality and performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The findings reported impact of online buzz valence on dependent variable, i.e., weekly box office revenue. In comparison, more recent studies reported in a blog analyses that box office ticket sales of movies can be affected by the valence of online buzz information collected from Yahoo Movie and blog posts (Gopinath, Chintagunta, and Venkataraman, 2013). Chen, Stephen (2001) in the research work of assessing the impact of internet on brands claims that easy access to online customer reviews has led some audiences (consumers) to suggest that alternative assurances of product quality and performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Failing to properly control for quality heterogeneity can lead to omitted variable bias or potential endogeneity between the movie's box office and the network embeddedness of its team members. To address this potential endogeneity, prior work suggests exploiting the panel data structure and incorporating movie-level fixed effects (Elberse 2007;Gopinath, Chintagunta, and Venkataraman 2013). However, only one observation of the cumulative revenue exists for each movie.…”
Section: Measures and Modelingmentioning
confidence: 99%
“…Quality perceptions consist of three components: (1) abstract dimensions of intrinsic attributes (e.g., safety, durability), (2) perceived monetary price, and 3) reputation formed through advertising and brand name [61]. 2 A few notable exceptions include [19,34,43,44,56]. But they collect online buzz data from a single source, such as a movie review site (e.g., Yahoo!Movie) [19,43], an online forum [34], or a single firm [56].…”
Section: Introductionmentioning
confidence: 99%
“…2 A few notable exceptions include [19,34,43,44,56]. But they collect online buzz data from a single source, such as a movie review site (e.g., Yahoo!Movie) [19,43], an online forum [34], or a single firm [56]. adjust their prices up or down by small increments [10].…”
Section: Introductionmentioning
confidence: 99%